The CARICOM Competition Commission : building competitive markets (CCS. CSME Unit BridgetownBB, 2008)
Seeks to inform and educate stakeholders in the CSME about the latest initiative in the developmen of the CSME generally, and specifically in the area of competition.
Keywords: COMPETITION POLICY